2013
DOI: 10.1177/1044207313486521
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Unmet Needs for Long-Term Care on Mortality Among Older Adults in China

Abstract: The unmet needs of persons needing long-term care have recently drawn attention in China, the nation with the world's largest elderly population. Using national panel data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), we examined the 3-year mortality of 3,089 Chinese adults above the age of 65 years who required long-term care. Long-term care needs were measured by the inability to perform any of the following six activities of daily living for 3 months: eating, dressing, bathing, getting in/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 43 publications
(39 reference statements)
1
52
2
2
Order By: Relevance
“…Using a sample of French residents, Dourgnon, Jusot, and Fantin () found a detrimental impact on health 4 years after having declined care for financial reasons. Zhen, Feng, and Gu () find an increase in 3‐year mortality among the elderly with unmet needs in China. Our study builds on this work using a panel survey of Canadians that includes a shorter time between surveys (2 years), a more generic measure of unmet need and a longer period, enabling us to better capture the effect of unmet need on future health.…”
Section: Introductionmentioning
confidence: 99%
“…Using a sample of French residents, Dourgnon, Jusot, and Fantin () found a detrimental impact on health 4 years after having declined care for financial reasons. Zhen, Feng, and Gu () find an increase in 3‐year mortality among the elderly with unmet needs in China. Our study builds on this work using a panel survey of Canadians that includes a shorter time between surveys (2 years), a more generic measure of unmet need and a longer period, enabling us to better capture the effect of unmet need on future health.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that older people with unmet needs face serious restrictions in life (e.g., not bathing as often as they want to, not eating when hungry or not getting housework done) (Allen & Mor, ; Allen, Piette, & Mor, ). In the longer term, unmet needs may lead to mental health problems (Choi & McDougall, ), acute care admission (Sands et al, ) or higher mortality rates (He et al, ; Zhen, Feng, & Gu, ). In order to improve the health outcomes of older people, it is important for governments to identify those older people with unmet needs and alleviate their negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, survey data suggest that most Chinese elderly (85-90 percent) want to and, in fact, receive care in their own homes from family members. 21 This pattern of family-based care provision is more evident in rural China, where families are larger (due to the earlier relaxation of the one-child policy) and both retirement pensions and healthcare facilities are less prevalent. According to one study, rural seniors were heavier users of informal care (91.8 percent) than urban seniors (87.7 percent).…”
Section: Home-based Carementioning
confidence: 97%